Novel Circovirus in Blood from Intravenous Drug Users, Yunnan, China - Yanpeng Li; Peng Zhang; Mei Ye; Ren-Rong Tian; Na Li; Le Cao; Yingying Ma; Feng-Liang Liu; Yong-Tang Zheng; Chiyu Zhang (Emerging Infectious Diseases, 2023)
We identified a novel circovirus (human-associated circovirus 2 [HuCV2]) from the blood of 2 intravenous drug users in China who were infected with HIV-1, hepatitis C virus, or both. HuCV2 is most closely related to porcine circovirus 3. Our findings underscore the risk for HuCV2 and other emerging viruses among this population.